Increased NAFLD risk in newly diagnosed patients with RA during the first 4 years of follow-up: a nationwide, population-based cohort study - Yi-Ming Chen; Tsai-Ling Liao; Hsin-Hua Chen; Der-Yuan Chen; Kuo-Tung Tang; Ching-Heng Lin; Wei-Li Ho; Po-Ku Chen; Shih-Hsin Chang (BMJ Open)
Background Although the non-alcoholic fatty liver disease (NAFLD) is prevalent in the general population, NAFLD risk in newly diagnosed rheumatoid arthritis (RA) has rarely been explored. In this population-based cohort, we examined NAFLD risk in patients with RA and identified the potential risk factors.Design Retrospective study.Setting Taiwan.Participants 2281 newly diagnosed patients with RA and selected 91 240 individuals without RA to match with patients with RA (1:40) by age, gender, income status and urbanisation level of the residence.Outcomes In this retrospective study using the 2000–2018 claim data from two-million representative Taiwanese population, we identified and compared the incidence rates (IRs) of NAFLD and alcoholic fatty liver disease (AFLD) between RA and non-RA groups. Using multivariable regression analyses, we estimated adjusted HR (aHR) of NAFLD development in patients with RA compared with individuals without RA, with 95% CIs.Results The incidences of NALFD and AFLD were not significantly different between individuals with RA and without RA during the 17-year follow-up period. However, patients with RA had significantly increased NAFLD risk during the first 4 years after RA diagnosis, with IR ratio of 1.66 fold (95% CI 1.18 to 2.33, p<0.005), but the risk was reduced after the first 4 years. Multivariable regression analyses revealed that aHR was 2.77-fold greater in patients not receiving disease-modifying anti-rheumatic drugs therapy than in non-RA subjects (p<0.05). Old age, women, low-income status and obesity could significantly predict NAFLD development.Conclusions We demonstrated elevated risk of NAFLD in patients with RA during the first 4 years after RA diagnosis, and old age, women, low-income status and obesity were significant predictors of NAFLD.